La curva de Phillips en Ecuador, periodo 2000-2008. - Zambrano Pesantez, Mario Daniel (My University, 2019)
Ecuador has undergone major changes in its economy over the years, this research is based on the analysis of one of the most important macroeconomic tools used to understand inflation, called the Phillips curve, which shows the relationship between the unemployment rate and inflation, in this case applied to the Ecuadorian case during the period 2000-2008, trying to emphasize the reason for the increase or decrease of these variables, taking into account the employment policies and monetary policies adopted by The Ecuadorian state. In order to carry out a more realistic analysis, data obtained from the Central Bank of Ecuador (ECB) will be used, taking into account that Ecuador has a small and open economy to be able to determine if the Phillips theory is fulfilled at the end of this work in our country.
Ecuador ha pasado por cambios importantes en su economía a lo largo de los años, la presente investigación se basa en el análisis de una de las herramientas macroeconómicas más importante utilizada para entender la inflación, llamada la curva de Phillips, la cual muestra la relación entre la tasa de desempleo y la inflación, en este caso aplicada para el caso Ecuatoriano durante el periodo 2000-2008, procurando hacer énfasis en el porqué del aumento o la disminución de estas variables, tomando en cuenta las políticas de empleo y políticas monetarias adoptadas por el estado ecuatoriano. Para poder llevar a cabo un análisis más realista, se recurrirá a datos obtenidos del Banco Central del Ecuador (BCE) esto teniendo en cuenta que Ecuador tiene una economía pequeña y abierta para poder al final de este trabajo determinar si se cumple la teoría de Phillips en nuestro país.
Keywords: CURVA DE PHILLIPS; INFLACIÓN; DESEMPLEO; ECUADOR